Lazarus. Volume 3, Conclave - Rucka, Greg (Image Comics, Inc., 2015)
The world now lies divided not amongst political or geographic boundaries but amongst financial ones. Wealth is power, and that power rests with only a handful of families. As alliances fray and allegiances are tested, these rulers of the world have gathered once more. A conclave has been called, bringing together the leaders, their advisors, and most perilously, their Lazari--the superhuman champions bound to the Families that created them--in one place. While a delicate dance of formality and politics takes place, the stakes are nothing less than world domination.